Association of contrast-induced nephropathy with bare metal stent restenosis in STEMI patients treated with primary PCI - Güngör, Barış; Karataş, Mehmet Baran; İpek, Göktürk; Özcan, Kazım Serhan; Çanga, Yiğit; Onuk, Tolga; Keskin, Muhammed; Hayıroğlu, Mert İlker; Karadeniz, Fatma Özpamuk; Sungur, Aylin; Öztürk, Recep; Bolca, Osman (Renal failure, 2016)
Background: Contrast induced nephropathy (CIN) has been proven as a clinical condition related to adverse cardiovascular outcomes. However, relationship between CIN and stent restenosis (SR) remains unclear. In this study, we aimed to investigate the association of CIN with SR rates after primary percutaneous coronary intervention (PCI) and bare metal stent (BMS) implantation. Methods: A total number of 3225 patients who had undergone primary PCI for STEMI were retrospectively recruited. The medical reports of subjects were searched to find whether the patients had a control coronary angiogram (CAG) and 587 patients with control CAG were included in the study. The laboratory parameters of 587 patients were recorded and patients who developed CIN after primary PCI were defined. Contrast induced nephropathy was defined as either a 25% increase in serum creatinine from baseline or 0.5 mg/dL increase in absolute value, within 72 h of intravenous contrast administration. Results: The duration between primary PCI and control CAG was median 12 months [8-24 months]. The rate of SR was significantly higher in CIN (+) group compared to CIN (−) group (64% vs. 46%, p < 0.01). In multivariate Cox regression analysis, male gender, stent length, admission WBC levels and presence of CIN (HR 1.39, 95% CI 1.06-1.82, p < 0.01) remained as the independent predictors of SR in the study population. Conclusion: Gender, stent length, higher serum WBC levels and presence of CIN are independently correlated with SR in STEMI patients treated with BMS implantation.